EFFECT OF PHENYL MERCURIC ACETATE ON CARBOHYDRATE CONTENT OF CHANNA PUNCTATUS - KARUPPASAMY, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
The glycogen and glucose contents in the liver, muscle, intestine, kidney and brain of Channa punctatus exposed to 0.106 and 0.40 ppm concentration of phenyl mercuric acetate (PMA) for short and long terms at an interval of 24, 72 and 120 hrs and 10, 20 and 30 days, respectively, have been studied. The observed results indicate that the reduction of both glycogen and glucose due to glycogenolysis and glycolysis to meet energy demand caused by PMA stress in both exposure periods.